2021
DOI: 10.3233/jad-200840
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Spatial Associations Between Amyloid-β Deposition, Grey Matter Volume, and Neuroinflammation in Alzheimer’s Disease

Abstract: Background: It has been proposed that amyloid-β (Aβ) plays a causal role in Alzheimer’s disease (AD) by triggering a series of pathologic events—possibly including neuroinflammation—which culminate in progressive brain atrophy. However, the interplay between the two pathological molecular events and how both are associated with neurodegeneration is still unclear. Objective: We aimed to estimate the spatial inter-relationship between neurodegeneration, neuroinflammation and Aβ deposition in a cohort of in 20 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 105 publications
2
18
0
Order By: Relevance
“…Accordingly, our results provide a tantalizing association between neuroinflammation and brain function, as measured for the first time, to the best of our knowledge, using BOLD activation, in a target region of known AD pathophysiology which shows a notable overlap between higher levels of Aβ and neuroinflammation 3 as well as altered functional brain response 10 , 13 , 14 at a mild AD stage.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Accordingly, our results provide a tantalizing association between neuroinflammation and brain function, as measured for the first time, to the best of our knowledge, using BOLD activation, in a target region of known AD pathophysiology which shows a notable overlap between higher levels of Aβ and neuroinflammation 3 as well as altered functional brain response 10 , 13 , 14 at a mild AD stage.…”
Section: Discussionmentioning
confidence: 53%
“…In fact, there is some evidence that puts the PCC as an excellent candidate for exploring the interplay between function and AD-related pathophysiological events. For instance, the PCC is a default mode network (DMN) region, involved in cognitive effort and episodic memory 7 , 8 , being also a hotspot for AD-related neuropathological burden 3 , 9 . Previous studies have indeed associated PCC with both early abnormal Aβ deposition 7 , 10 and increased neuroinflammation 3 , 11 , possibly due to its high synaptic activity, which increases the need for adequate autophagic response in order to maintain synaptic homeostasis 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies focus on gray matter of the brain, where correlations between cortical volumes and age have been consistently described. These findings provide evidence of heterogenous patterns of normal age-related changes (3)(4)(5)(6)(7)(8), with detectable differences in neurological diseases and disorders (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 74%
“…A large body of magnetic resonance imaging (MRI) research has shown that the structure of the human brain is constantly changing with age. In the gray matter, structural MRI studies have shown heterogenous patterns of normal agerelated changes in cortical volume and thickness [23][24][25][26][27][28][29][30], with detectable differences in abnormal aging and disease [30][31][32][33][34][35]. In the white matter, diffusion tensor imaging (DTI) analysis has shown that fractional anisotropy (FA) is negatively associated with age and mean diffusivity (MD) is positively associated with age across several white matter pathways [36][37][38][39], and tractography analysis has shown that the volume and surface areas of many pathways decreases with age [40].…”
Section: Introductionmentioning
confidence: 99%